NOX family NADPH oxidases in mammals: Evolutionary conservation and isoform-defining sequences - Bahareh Nazari; Vincent Jaquet; Karl-Heinz Krause (Redox Biology, 2023)
NADPH oxidases are superoxide-producing enzymes that play a role in host defense, biosynthetic pathways, as well as cellular signaling. Humans have 7 NOX isoforms (NOX1-5, DUOX1,2), while mice and rats lack NOX5 and therefore have only 6 NOX isoforms. Whether all human NOX isoforms or their subunits (CYBA, NCF1, 2, 4, NOXO1, NOXA1, DUOXA1, 2) are present and conserved in other mammalian species is unknown. In this study, we have analyzed the conservation of the NOX family during mammalian evolution using an in-silico approach. Complete genomic sequences of 164 mammalian species were available. The possible absence of genes coding for NOX isoforms was investigated using the NCBI orthologs database followed by manual curation. Conservation of a given NOX isoform during mammalian evolution was evaluated by multiple alignment and identification of highly conserved sequences. There was no convincing evidence for the absence of NOX2, 3, 4, and DUOX1, 2 in all the available mammalian genome. However, NOX5 was absent in 27 of 31 rodent, in 2 of 3 lagomorph and in 2 out of 18 bat species. NOX1 was absent in all sequenced Afrotheria and Monotremata species, as well as in 3 of 18 bat species. NOXA1 was absent in all Afrotheria and in 3 out of 4 Eulipotyphla species. We also investigated amino acid sequence conservation among given NOX isoforms. Highly conserved sequences were observed for most isoforms except for NOX5. Interestingly, the highly conserved region of NOX2 sequence was relatively small (11 amino acids), as compared to NOX1, 3, 4.The highly conserved domains are different from one NOX isoform to the other, raising the possibility of distinct evolutionary conserved functional domains. Our results shed a new light on the essentiality of different NOX isoforms. We also identified isoform-defining sequences, i.e., hitherto undescribed conserved domains within specific NOX isoforms.